2019
DOI: 10.1158/1078-0432.ccr-17-3553
|View full text |Cite
|
Sign up to set email alerts
|

SS18-SSX–Dependent YAP/TAZ Signaling in Synovial Sarcoma

Abstract: Purpose: Synovial sarcoma is a soft tissue malignancy characterized by a reciprocal t(X;18) translocation. The chimeric SS18-SSX fusion protein acts as a transcriptional dysregulator representing the major driver of the disease; however, the signaling pathways activated by SS18-SSX remain to be elucidated to define innovative therapeutic strategies.Experimental Design: Immunohistochemical evaluation of the Hippo signaling pathway effectors YAP/TAZ was performed in a large cohort of synovial sarcoma tissue spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…Verteporfin effectively reduced U-2OS cell viability, with an IC50 value of 1.44 ± 0.46 μM. As demonstrated in other tumors, including synovial sarcoma [25], verteporfin led to a dose- and time-dependent reduction in the expression (Fig. 4a) and activity (Fig.…”
Section: Resultssupporting
confidence: 58%
“…Verteporfin effectively reduced U-2OS cell viability, with an IC50 value of 1.44 ± 0.46 μM. As demonstrated in other tumors, including synovial sarcoma [25], verteporfin led to a dose- and time-dependent reduction in the expression (Fig. 4a) and activity (Fig.…”
Section: Resultssupporting
confidence: 58%
“…Other pediatric sarcomas such as rhabdomyosarcoma, osteosarcoma, and neuroblastoma have been reported to express YAP1 and TAZ, with an impact on patient prognosis and conferring resistance to current therapies [37][38][39][40][41]. Moreover, recent studies have revealed that YAP1/TAZ are key signaling mediators of the oncogenic fusion genes in synovial sarcoma, myxoid liposarcoma, and alveolar rhabdomyosarcoma [42][43][44]. This positive functional cooperation in translocated sarcomas contrasts with the antagonism between YAP1/TAZ and EWS-FLI1 that we have observed in EwS.…”
Section: Discussionmentioning
confidence: 99%
“…In alveolar rhabdomyosarcoma, the chimeric PAX3-FOXO1 oncoprotein was found to promote tumorigenesis by inhibition of MST1, and dysregulation of YAP1 8 . We previously described an oncogenic mechanism of aberrant YAP1/Hippo signaling activation mechanistically based on the FUS-DDIT3 33 and SS18-SSX 34 oncoproteins in MLS and SySa which is to some extent reminiscent of the situation in alveolar rhabdomyosarcoma in which the pathognomonic PAX3-FOXO1 protein promotes tumorigenesis by Hippo pathway suppression 8 .…”
Section: Discussionmentioning
confidence: 99%